Preparation and Performance of a Fixed Bed Catalyst for the Oxidation of Sodium Mercaptides - Wang Heming; Liu Xianshang; Zhu Lijun; Zhou Yulu; Xia Daohong (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The activated-carbon supported cobalt pthalocyanine as a fixed bed catalyst (CoPc/C) was prepared by impregnation method and its performance on the oxidation of sodium mercaptides in light oil sweetening was investigated. The FTIR, XRD, and SEM analysis indicated that the active component dispersed well on the carrier and the results of the TG analysis showed that CoPc/C has good thermostability. It was tested that the prepared catalyst has a high catalytic activity towards sodium mercaptides. The removal rate of n-C4H9SNa was up to 100 % and for t-C4H9SNa, was 87.5% at a reaction time of 30 min. With the reaction temperature raised from 20 °C to 60 °C at intervals of ten degrees, the oxidation rate increased obviously, especially in the first ten minutes. A kinetic model mainly related to the transfer process was supposed. The catalyst CoPc/C had a good anti-loss performance of the active component both in water and alkali liquor when used. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)